Antihyperglycemic and anti-oxidant activity of various fraction of Parmotrema hababianum in streptozotocin-induced diabetic rat (Bangladesh Journal of Pharmacology, 2016)
The core objective of this study was to investigate the in vitro anti-oxidant and antihyperglycemic effect of the ethanol extract of Parmotrema hababianum in streptozocin-induced diabetic rats for 42 days. The extract showed nearly all anti-oxidant activities with maximum presence. The treatment with extract in diabetic rats at the dosage level of 100 and 200 mg/kg, which is compared with diabetic control and glibenclamide at a dosage level of 4 mg/kg and the biochemical parameters such as blood glucose, total cholesterol, triglycerides, HDL, LDL, insulin, total protein, urea and creatinine were assessed. The extract showed positive correlation (p